2012
DOI: 10.1371/journal.pone.0035982
|View full text |Cite
|
Sign up to set email alerts
|

What Parents of Children Who Have Received Emergency Care Think about Deferring Consent in Randomised Trials of Emergency Treatments: Postal Survey

Abstract: ObjectiveTo investigate parents’ views about deferred consent to inform management of trial disclosure after a child’s death.MethodsA postal questionnaire survey was sent to members of the Meningitis Research Foundation UK charity, whose child had suffered from bacterial meningitis or meningococcal septicaemia within the previous 5 years. Main outcome measures were acceptability of deferred consent; timing of requesting consent; and the management of disclosure of the trial after a child’s death.Results220 fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
61
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 12 publications
8
61
2
Order By: Relevance
“…However, our results are consistent with other evidence indicating the acceptability of deferred consent to parents and to practitioners with experience of the process. 13,19,20 The higher consent rate for emergency compared with elective admissions may reflect a greater capacity for informed decision-making when parents were approached after the medical emergency had taken place, in a potentially less stressful environment. For elective admissions, parents may have felt responsible for…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, our results are consistent with other evidence indicating the acceptability of deferred consent to parents and to practitioners with experience of the process. 13,19,20 The higher consent rate for emergency compared with elective admissions may reflect a greater capacity for informed decision-making when parents were approached after the medical emergency had taken place, in a potentially less stressful environment. For elective admissions, parents may have felt responsible for…”
Section: Discussionmentioning
confidence: 99%
“…11 Legislation introduced in the United Kingdom in 2008 allows the use of deferred consent for studies involving children provided that treatment is urgently needed, urgent action is needed for the purposes of the trial, it is not reasonably practicable to obtain consent prospectively, and an ethics committee has given approval to the procedure under which the action is taken. 12,13 However, there is a lack of evidence for the acceptability, design, and conduct of deferred consent in children, particularly relating to complex situations such as the death of a child.…”
Section: What This Study Addsmentioning
confidence: 99%
See 1 more Smart Citation
“…Professionals without previous experience of deferred consent have been found to be apprehensive about the approach or find it inappropriate not to give parents any choice before starting the study. 35,39 On the other hand, approximately two-thirds of parents of critically ill children reported that deferred consent was acceptable to them, 41 or parents suggest that professionals should just get on with treating their child and worry about consent later. 39 These different viewpoints indicate the need for further discussion and reflection on the best practice regarding the informed consent process and to consult with parents (and, if feasible, young people) as partners in the design of consent procedures for trials that will be implemented in emergency settings.…”
Section: Iii2 Potential Solutionsmentioning
confidence: 99%
“…Research suggests that parents favour deferred consent over waived consent and consider it an acceptable alternative to informed consent for emergency situations [59,60]. In a study by Woolfall et al [60], parents suggested it would be advisable for the researchers to seek advice from the bedside nurse to establish the moment when the child's condition was stable and then ask for consent.…”
Section: Deferred Consentmentioning
confidence: 99%